Low Temperature Features of Sound Velocity in Fullerite C[60] Orientational Glasses; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Barabashko M. S. Maksim Sergeevich (2017, 2017)
Title screen